PENERAPAN PERHITUNGAN, PENYETORAN, DAN PELAPORAN PPN PADA LEMBAGA MANAJEMEN ASET NEGARA - Alaika Febriansya (2022)
Value Added Tax is an indirect tax that occurs as a result of the delivery of taxable goods or taxable services so that taxes are owed on these transactions. The related tax data in this Final Project is taken from the State Asset Management Institute (LMAN) which is a Public Service Agency owned by a government agency that has been confirmed as a taxable entrepreneur, where one of the business activities carried out is the Management of State Property (BMN), which includes leasing activities of property assets. The purpose of this final report is to find out the application of calculation, deposit, and reporting of VAT on apartment leasing activities by LMAN which produces output tax and cannot be credited. The DPP calculation uses the rental price which is calculated based on the rental rate stipulated in the applicable Minister of Finance Regulation. The entire process of depositing and reporting VAT is carried out using an electronic system so that in practice there is little possibility of input errors, both identity and the value of the tax payable. Overall, the calculation, deposit, and reporting of VAT carried out by LMAN is in accordance with the provisions of the applicable laws and regulations.